Congenital malformation of fifth lumbar vertebra: A case report - Khanna, Jugesh; Chauhan, Renu (International Journal of Research in Medical Sciences, 2017)
Fifth lumbar vertebra is an atypical vertebra as it has widely separated inferior articular processes and thick transverse processes projecting out from the body and pedicles of the vertebra. On routine examination of osteology specimens we found a fifth lumbar vertebra in two separate parts. One part consisted of body, pedicles, transverse and superior articular processes. The other part consisted of lamina, spinous and inferior articular processes. Knowledge of this variation may be of importance to the clinicians for diagnosis of certain neurological deficits in the lower limb and to orthopaedic surgeons and neurosurgeons during the surgical intervention of that area.